Epileptiform activity influences theta-burst induced LTP in the adult hippocampus: a role for synaptic lipid raft disruption in early metaplasticity? - Carvalho-Rosa, José D.; Rodrigues, Nádia C.; Silva-Cruz, Armando; Vaz, Sandra H.; Cunha-Reis, Diana (Frontiers in Cellular Neuroscience, 2023)
Non-epileptic seizures are identified as a common epileptogenic trigger. Early metaplasticity following seizures may contribute to epileptogenesis by abnormally altering synaptic strength and homeostatic plasticity. We now studied how in vitro epileptiform activity (EA) triggers early changes in CA1 long-term potentiation (LTP) induced by theta-burst stimulation (TBS) in rat hippocampal slices and the involvement of lipid rafts in these early metaplasticity events. Two forms of EA were induced: 1) interictal-like EA evoked by Mg2+ withdrawal and K+ elevation to 6mM in the superfusion medium or 2) ictal-like EA induced by bicuculine (10M). Both EA patterns induced and LTP-like effect on CA1 synaptic transmission prior to LTP induction. LTP induced 30 min post EA was impaired, an effect more pronounced after ictal-like EA. LTP recovered to control levels 60 min post interictal-like EA but was still impaired 60 min after ictal-like EA. The synaptic molecular events underlying this altered LTP were investigated 30 min post EA in synaptosomes isolated from these slices. EA enhanced AMPA GluA1 Ser831 phosphorylation but decreased Ser845 phosphorylation and the GluA1/GluA2 ratio. Flotillin-1 and caveolin-1 were markedly decreased concomitantly with a marked increase in gephyrin levels and a less prominent increase in PSD-95. Altogether, EA differentially influences hippocampal CA1 LTP thorough regulation of GluA1/GluA2 levels and AMPA GluA1 phosphorylation suggesting that altered LTP post-seizures is a relevant target for antiepileptogenic therapies. In addition, this metaplasticity is also associated with marked alterations in classic and synaptic lipid raft markers, suggesting these may also constitute promising targets in epileptogenesis prevention.